Brown vs. Board of Education of Topeka and its influence on the the brazilian structural injunction: : restricted and strategic use (Revista do Tribunal Regional Federal da 3ª Região, 2023)
This study has as its problem the analysis of the influence of Brown v. Board of Education of Topeka for the construction of the Brazilian structural injunction, having as assumption the viability of this procedural way to be used in our legal system. The hypothesis of the research is that, in light of relevant procedural aspects extracted from Brown, the structural injunction can be employed in Brazil, as long as in a restricted and moderate manner, for which it is necessary: 1) to verify a state of affairs (unconstitutional or illegal) or eloquent nonconformity, of extreme gravity and unwanted by the majority of society exhausted with the structural problem and with executive and legislative authorities (even if supported by segments of that same society) be verified; 2) to selected a strategic case, combining elements of the multi-polarity of those involved and the judicial structure itself, skillful and culturally prepared for the construction of negotiations, with intra and inter-institutional dialogue capable of defining viable solutions and systematically monitored in successive equally dialogic phases, allowing for reinforcements, complements and revisions; and 3) set a clear and defined objective, but flexible, so that its processing does not get lost in undetermined new goals and measures, so that it must have progressive phases (from the general to the particular) with the delegation of minor decision-making and executive attributions to ordinary instances. The widespread use of this procedural path, driven by voluntarism, activism and the like, can disallow this useful mechanism of judicial protection. To prove the hypothesis, the inductive method is employed.
Keywords: U.S. Supreme Court; Brown v. Board of Education of Topeka; Structural injunction; Strategic litigation; Influence